Government of Rajasthan Draft Annual Plan 1995-96 Planning Department - Planning Commission (Planning Commission, 1995)
Education is recognised to be a major influence in quick social transformation. In view of the social backwardness inherited by the State from its constituent princely States, expansion of education facilities has been receiving pointed attention under the State's developmental plans. Rajasthan is already devoting about 17 percent of its budget for education. Despite this, literacy rate in Rajasthan is nearly 38.6 per cent which is only next to Bihar (38.5 per cent) from the bottom. The all India average is 52.1 per cent. Female literacy in Rajasthan is, however, the lowest (20.4 per cent) in the country. The all India average of female literacy is 39.3 per cent. The literacy rate in SC/ST women is abysmally low. The State's efforts made in this direction therefore, need not only to be continued but accelerated.
Draft Annual Plan 1995-96
Government of Rajasthan